If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -14 = 2(2x + 3) Reorder the terms: -14 + 2x = 2(2x + 3) Reorder the terms: -14 + 2x = 2(3 + 2x) -14 + 2x = (3 * 2 + 2x * 2) -14 + 2x = (6 + 4x) Solving -14 + 2x = 6 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -14 + 2x + -4x = 6 + 4x + -4x Combine like terms: 2x + -4x = -2x -14 + -2x = 6 + 4x + -4x Combine like terms: 4x + -4x = 0 -14 + -2x = 6 + 0 -14 + -2x = 6 Add '14' to each side of the equation. -14 + 14 + -2x = 6 + 14 Combine like terms: -14 + 14 = 0 0 + -2x = 6 + 14 -2x = 6 + 14 Combine like terms: 6 + 14 = 20 -2x = 20 Divide each side by '-2'. x = -10 Simplifying x = -10
| 9x-7=23x-14 | | x-2.6=7.3 | | 27=46+2x-1x | | 1.5m=0.5 | | -6x-21+9x=42 | | 2x+6=-7x-9 | | 27-(x+9)=4x-2 | | 6x-(2x+4)-(x+3)= | | 7(2y+1)=2(y-13) | | 0.4=0.75+y | | -6b+5(1-b)=-8b+26 | | (2x-1)(x^2-3x+5)=0 | | 3(2x+1)+1+2x=3(2x+2)+x | | 2X^2-16X+64= | | 7y-9-4y+4=0 | | 1.2x=40.8 | | 0(2x-4)^-11/2 | | -5+x-9=15 | | -1/4a7/4a=-21 | | 3/5x-3=2.25 | | 0.4=0.75y | | -(-5-6n)-3(2n+3)=3 | | 3x+4=-2x-14 | | -12-1x=8-3x | | 5x-3y=10fory | | -6=m+(-25) | | 3x/4=2 | | 1.8q-4.3-2.3q=-1.5q-4.6 | | -6=my+(-25) | | 7x^2-21x+0=0 | | X+8+7=2x+15 | | 108=-4(-6x-3) |